Modified properties of a glycated and cross‐linked soy protein isolate by transglutaminase and an oligochitosan of 5 kDa. (23rd March 2016) - Fu, Miao; Zhao, Xin‐Huai
Abstract: BACKGROUND: Soy protein is an important protein ingredient for the food industry; however, its properties can be improved by enzymatic and chemical modifications. This study applied a new enzymatic glycation and cross‐linking to modify soy protein isolate (SPI), using an oligochitosan of 5 kDa and transglutaminase. Properties of the obtained glycated and cross‐linked SPI (GC‐SPI) were unknown and thus assessed. RESULTS: GC‐SPI contained glucosamine of 13.6 g kg −1 protein, but less reactable &bond;NH2 than SPI (0.42 vs. 0.50 mol kg −1 protein). Infrared spectra and circular dichroism results showed that GC‐SPI other than SPI and cross‐linked SPI had more &bond;OH in molecules, and was more disordered in secondary structure. In comparison with SPI, GC‐SPI showed enhanced water‐binding capacity, could form aggregates with enlarged hydrodynamic radius (180.2 vs. 82.9 nm) and negative zeta‐potential (−31.2 vs. −27.7 mV) in dispersion, but exhibited lower thermal stability (e.g. greater mass loss) upon heating at a temperature above 288 °C. GC‐SPI also had lower in vitro proteolytic digestibility than SPI due to the protein cross‐linking. CONCLUSION: Oligochitosan of 5 kDa and transglutaminase can be used to glycate and cross‐link SPI. This approach is applicable to generate potential protein ingredient with good hydration and dispersive stabilisation. © 2016 Society of Chemical Industry